(646) The Reform of the Financial System of State-owned Enterprises in Poland إصلاح النظام المالي للمؤسسات المملوكة للدولة في بولندا - Fedorowicz, Zdzislaw (INP, 2024)
Discusses the reform of the financial system of state-owned enterprises in Poland, where directives were replaced by new parameters within the planning and management system of socialist enterprises. The reform was implemented in 1965 and put into practice on January 1, 1966, with the aim of increasing the influence of incentives and stimulating economic activity within the existing institutional framework. The most significant changes occurred in the distribution of profits of state-owned enterprises, where the general principle of dividing net profits among workers (bonus fund), the enterprise (development fund), and the trust (transfers to the trust, from which a portion of the aggregated net profit is returned to the state budget) remained unchanged, but the principles of forming these parts were significantly altered. These changes are linked to the system of directives and parameters transferred to enterprises by the central planning authority based on the annual national economic plan. In the new system, the most important directive given to enterprises is the target rate of net profit to be achieved within the planned period. Enterprises must establish their economic plans to ensure that their activities yield financial results that meet or exceed the directive rate. Currently, the system of mandatory net profit rates related to global production costs prevails, while rates related to engaged capital are still being experimented with, but are expected to be introduced more broadly in the future.